ACHIEVING ENERGY SAVING BY USING AUTOMATION SYSTEMS IN TECHNOLOGICAL PROCESSES OF ENTERPRISES - Vakhobova Sojida Komiljonovna,; Erkinov Akobirbek Akmaljon ugli, (Research Focus International Scientific Journal, 2024)
The article collects and analyzes data that determines the real state of the enterprise's energy economy, a program of measures to save electricity that determines the essence of energy activities, as well as the rational organization of the enterprise's activities on the basis of organizational ones, and presents legal and technical activities.